Expression and localization of SLC9A2 and SLC9A3 sodium hydrogen exchangers and their possible role in acid-base regulation in freshwater rainbow trout (Oncorhynchus mykiss) - Ivanis, Goran (University of Ottawa (Canada), 2008)
Teleost fish, like other vertebrates, maintain blood pH at a constant value, with the gills and kidney being major sites of regulation. This thesis examines the involvement of two members of the Na+/H + exchange (NHE) gene family, NHE2 and NHE3 in branchial and renal acid-base regulation in freshwater rainbow trout (Oncorhynchus mykiss ). Using homology cloning techniques and mining of genomic databases, genes orthologous to NHE2 (trout NHE2) and NHE3 (trout NHE3a and NHE3b) were described and characterized. Applying a variety of techniques including immunocytochemistry, in situ hybridization, Western blotting and real-time PCR, I demonstrated that NHE2 and NHE3 are the predominant gill and kidney isoforms, respectively. In the gill, NHE2 and NHE3 are expressed in a subset of mitochondria rich cells (MRCs) termed PNA+ (peanut lectin agglutinin) MRCs. NHE2 mRNA levels were significantly increased during ambient hypercapnia, responses that may have been linked to elevated levels of plasma cortisol. In the kidney, NHE3 appeared to be localized to the apical membrane of proximal tubule cells where it is presumed to play an important role in HCO3- reabsorption. In support of its role in HCO3- reabsorption, renal NHE3 mRNA expression and protein levels were significantly increased during hypercapnia, responses that may have been cued by elevated plasma cortisol.
Keywords: Biology, General.; Biology, Molecular.